Cover Image, Volume 52, Issue 2. (1st April 2019) - Wang, Qingxuan; Zhou, Chenchen; Li, Xiaobing; Cai, Linyi; Zou, Jing; Zhang, Demao; Xie, Jing; Lai, Wenli
Abstract : The cover image is based on the Original Article TGF‐β1 promotes gap junctions formation in chondrocytes via Smad3/Smad4 signalling by Qingxuan Wang et al., https://doi.org/10.1111/cpr.12544 .